초등학교 통합학급에서 교사의 교육적 지원을 통한 자폐아동의 학교생활 변화 연구 - 김진선, 정혜영 (교과교육학연구, 2008)
본 연구는 일반아동과 장애아동의 물리적 통합이 실시되고 있는 초등학교 일반 학급에서 사회 적, 교육과정 통합이 어떻게 시도되는지 살펴보고자 하였다. 담임교사의 교육적 지원을 통해 초등 학교 3학년 남자 자폐아동의 학교생활이 어떻게 변화되어 가는지 탐색하고자 예비관찰과 집중관 찰, 면담 등을 활용한 사례연구를 실시하였다. 예비관찰 시기였던 물리적 통합단계에서는 아동은 자폐적 특성을 그대로 드러냈지만, 담임교사에 의해 교육적 지원이 제공된 사회적 통합과 교육과 정 통합의 단계에서는 자폐아동에게 많은 변화가 나타났다. 담임교사가 자폐아동을 위해 제공한 교육적 지원은 생활면과 학업면으로 다양한 프로그램이 제공되었다. 학교생활의 변화과정을 살펴 볼 때, 자폐아동의 학습능력이 향상되었고 혼자만의 일방적 상호작용에서 함께 하는 쌍방적 상호 작용으로 점차 변화되어갔다. 또한 공격적, 방어적 태도가 줄어들고 협동심과 자립심이 증가하여 통합학급 내에서 자폐아동의 학교생활이 긍정적으로 변화되어가는 모습을 보여주었다. 또한 실제 적인 통합교육이 되려면 교사의 애정과 관심, 적절한 교육적 개입이 필수적이며, 자폐아동을 둘러 싼 관련인과의 협력관계, 자폐아동 및 그 학급아동 간의 쌍방적 상호이해를 위한 시도가 함께 이루 어져야 함을 지적하였다. The study was to investigate the changing process of an autistic child's life at school through a qualitative research. A boy who has been diagnosed as an Autism, was selected. In order to get the resources, general observation and in-depth interviews were employed. The results of the study were as follows. First, the changing process of the autistic child's life at school was observed in the stage of physical integration with no educational support. In the stage of physical integration, where the class was integrated for the sake of qualitative integration of the child, there was no educational support offered; the child revealed his autistic tendencies. Second, the educational support was given in the academic aspect. The school subjects were revised and all those efforts were made as the investigator got together with a special teacher to discuss the curriculums at the Curriculum Revisions Council and to revise the curriculum of cooperative learning-based social studies and that of science for the child with autism. Third, there were changes to him both in the academic and behavioral characteristics aspect after the educational support was given. The changes were as follows; in the academic aspect, the negative sides of the child revealed in the early semester gradually disappeared as the educational support was given. Thus, the results showed that his learning abilities increased, his own one-way interactions changed to the two-way interactions, his aggressive and defensive attitudes decreased, and his cooperation and autonomy increased. In the integrated class, the autistic child's school life went through very positive changes. KCI Citation Count: 6